2013
DOI: 10.1155/2013/618269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Narrow Band Ultraviolet B Therapy versus Methotrexate on Serum Levels of Interleukin-17 and Interleukin-23 in Egyptian Patients with Severe Psoriasis

Abstract: Background. There is raised interest in the involvement of interleukin-(IL-)23/T-helper 17 cells (Th17) axis in the pathogenesis of psoriasis. Objectives. To compare the effect of narrow band ultraviolet B (NB-UVB) and methotrexate (MTX) therapy on serum levels of IL-17 and IL-23 in psoriatic patients. Methods. Thirty patients with severe plaque psoriasis were included: 15 patients received NB-UVB three times weekly (group I) and 15 patients received MTX 0.3 mg/kg per week (group II), both for 8 weeks. Before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…The increased serum level of IL-23 in PsA patients compared to the levels in controls probably reflects the contribution of IL-23 to the pathogenesis of PsA via the IL-23/IL-17 axis, which ultimately leads to psoriatic plaques, pannus formation, joint erosion and new bone formation [2,35,36]. In this context several studies have found elevated serum IL-23 levels in patients with SpA, PsO and PsA [37][38][39][40][41][42]. Therefore, close control of inflammation by anti-IL-23 drugs may turn off the disease activity and consequently the structural damage [5,9,10,43].…”
Section: Discussionmentioning
confidence: 99%
“…The increased serum level of IL-23 in PsA patients compared to the levels in controls probably reflects the contribution of IL-23 to the pathogenesis of PsA via the IL-23/IL-17 axis, which ultimately leads to psoriatic plaques, pannus formation, joint erosion and new bone formation [2,35,36]. In this context several studies have found elevated serum IL-23 levels in patients with SpA, PsO and PsA [37][38][39][40][41][42]. Therefore, close control of inflammation by anti-IL-23 drugs may turn off the disease activity and consequently the structural damage [5,9,10,43].…”
Section: Discussionmentioning
confidence: 99%
“…(Rentenaar et al 2004) [18] Furthermore, methotrexate therapy was shown to be associated with reduction of serum interleukin-17 and 23 levels in psoriasis patients. (Elghandour et al 2013) [19] It was suggested that methotrexate suppresses IL17 mRNA expression thereby decreasing IL-17 production. (Li et al 2012) [4] A signi cant percentage of our patients achieved a PASI 75 response.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that certain gene polymorphisms involved in the pathogenesis of psoriasis may allow to select patients likely to respond to methotrexate. (Warren et al 2009) [5] IL-17A and IL-17F genes are located on chromosome 6p12. (Park et al 2005;Prieto-Perez et al 2015) [6,7] Several IL17 gene polymorphisms have been described in literature and were associated with risk of developing several autoimmune, in ammatory and infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Our results correspond with other studies in other diseases treated with MTX monotherapy, such as juvenile idiopathic arthritis, rheumatoid arthritis (RA) or psoriasis, which also found a pre-existent higher concentration of TNFα in non-responders, 20 or lack of effect of MTX monotherapy on IL-23 or IL-17 serum or plasma concentrations. 29 30 Together, this may explain why MTX is not effective in patients with PsA with primarily IL-23-driven disease. Surprisingly, we also found consistently higher serum levels of the anti-inflammatory cytokine IL-10 in our non-responders.…”
Section: Discussionmentioning
confidence: 99%